Contralateral Minimally Invasive Laminectomy for Resection of a Synovial Cyst: 2-Dimensional Operative Video. Issue 1 (10th September 2019) - Mueller, Kyle; Fayed, Islam; Spitz, Steven; Nair, Nathan; Voyadzis, Jean-Marc; Sandhu, Faheem A
Abstract: Synovial cysts of the lumbar spine result from degeneration of the facet capsule, and their prevalence may be as high as 10% in symptomatic patients. Although conservative management is possible, the majority of patients will require resection. Traditional procedures for resection use an ipsilateral approach requiring partial or complete resection of the ipsilateral facet complex, possibly leading to further destabilization. A contralateral technique using minimally invasive tubular retractors for synovial cyst resection avoids facet disruption, minimizes soft-tissue trauma, and limits disruption of the ligamentous and bony structures. Additionally, by approaching contralateral, the cyst/dura interface is better visualized especially at the depths of the lateral recess. Seeing the full extent of this interface from an ipsilateral approach is very difficult without decompressing the cyst, which, in turn, makes dissecting and separating the remaining cyst wall more difficult and increases the risk of durotomies. 1, 2 We report the case of a 53-yr-old female who presented with persistent left leg pain in an L5 distribution that was associated with some mild lower back pain. She was refractory to conservative management that included physical therapy along with a series of epidural steroid injections. She was noted to have some weakness with dorsiflexion on the left side and as absent a straight leg raise. Given the predominance of her leg over her back symptoms along with the patient's age, a minimally invasive contralateral approach for resection of the synovial cyst was offered as opposed to more traditional decompression and fusion. Institutional Review Board approval and patient consent for solitary case reports are not needed at our institution.